Determination of PEG (Polyethlenee Glycol) Concentration and Dosage to Evaluate The Resistance of Rice (Oryza Sativa L.) to Drought - Siti Raihanun; M. Taufik Fauzi; Suwardji Suwardji; A.A.K Sudharmawan (Jurnal Biologi Tropis, 2023)
The writing is intended to assess the response of rice plants to the germination phase through induce concentrations and a dose of the PEG. Library research is used in this writing by locating and collecting libraries that were generated by earlier research. As for the data obtained in this writing, it is the result of analysis of various vets and rice varieties of Cempo Laut, Edok, Mutant Galurses (M5-GR150 1-4, M5-GR150 1-9, M5-GR200 1-2, M5-GR150 2-2, M5-GR150 2-3), Legowo, Malihan Ketan, Mlarak 1, Inpago, IR 64, Palenok, Philips, Radix. Concentrations of PEG 6000 and 8000 with a dose of 0%, 5%, 15%, 20% and 25% induced, then treated with the best denunciation. Observation data indicate that each response is different. PEG concentration of 8000 and dose of -0.5 MPa gave the best germination power.